Influence of Psychological Factors in Federated Futsal and Lifeguard Athletes, Differences by Gender and Category - Cano-Noguera, Francisco; Ibáñez-Pérez, Ricardo José; Cavas-García, Francisco; Martínez-Moreno, Alfonso (Frontiers in Psychology, 2021)
This research aims to analyse the differences in optimism, engagement and competitive anxiety as a function of the sport modality practised in lifeguarding (individual sport) and futsal (team sport); the sport category by age (cadet or youth) and gender. The LOT-R optimism questionnaire, the Connor-Davidson Resilience Scale (CD-RISC-10), the Utrecht Work Engagement Scale (UWES) and the Competitive Anxiety Scale (SAS-2) were applied to a sample of 189 participants (139 men and 50 womwn) aged between 14 and 17 years. The following statistical tests are performed: Cronbach's alpha, Pearson's linear correlation, Student's t-test, Kolmogorov-Smirnov test, Levene's test and multivariate linear regression. The data indicate that there are significant gender differences in total anxiety (p<0.001) and all its dimensions (somatic, worry, worry-free), also in optimism and pessimism (p<0.001), as well as in total engagement (p=0.051) and the absorption dimension (p<0.001). When comparing the sample by sport categories, there are statistically significant differences in somatic anxiety (p=0.036) and deconcentration (p=0.034), as well as in LOT-total (p=<0.001) and pessimism (p=<0.001). In relation to the sport modalities, lifeguards show more anxiety 38.39 (0.49) and more commitment 4.58 (0.87) while futsal athletes reach higher scores in deconcentration 8.45 (2.29). It is concluded that the variables of commitment and resilience had a statistically significant positive effect, and the category of < 16 years had a statistically significant negative effect, so the lower the category, the higher the optimism.